Pandemics and soft power: HIV/AIDS and Uganda on the global stage. Issue 3 (November 2020) - Doyle, Shane
Abstract: The COVID-19 outbreak of 2020 threatened years of effort by the Chinese authorities to extend its influence around the world. This article seeks to enhance understanding of China's defensive engagement with global health agencies, and more broadly of the relationship between pandemics and soft power, through an analysis of Uganda's evolving response to HIV/AIDS. As with COVID-19, HIV/AIDS presented a fundamental threat not only to countries' internal social stability and population health, but also to governmental legitimacy and nation-states' international reputation. HIV, however, also provided Uganda with an opportunity to enhance its global standing, influence international policy, and achieve national reconstruction. This case study highlights the importance of viewing international affairs from the perspective of the Global South. It argues that the very weakness of Uganda, and the structural marginality of HIV/AIDS, provided the leverage which would in the end deliver radical shifts within global health.